Management of Post-Extraction Orthodontic Relapse Using Miniplate Anchorage: A Case Report - Prakash, A. T. (2026)
Orthodontic relapse, particularly after extraction-based treatment and compromised anchorage control situation, remains a clinical as well as esthetic challenge. This case report presents the successful re-treatment of a 24-year-old female patient with a relapsed malocclusion, proclined incisors, molar crossbites, and lip protrusion, following prior fixed orthodontic therapy with extraction of four premolars. Miniplate-assisted maxillary arch distalization was employed to accomplish en-masse retraction, correct molar relationship, and improve facial profile. The use of temporaray skeletal anchorage device such as miniplates imparted steady, compliance-free mechanics, ensuing enhanced dental occlusion and soft tissue harmony. Here we highlight the effectiveness of miniplate-based mechanics in complex retreatment circumstances where traditional anchorage generally proves to be inefficient.